2016
DOI: 10.1098/rsob.150155
|View full text |Cite
|
Sign up to set email alerts
|

Notch stimulates growth by direct regulation of genes involved in the control of glycolysis and the tricarboxylic acid cycle

Abstract: Glycolytic shift is a characteristic feature of rapidly proliferating cells, such as cells during development and during immune response or cancer cells, as well as of stem cells. It results in increased glycolysis uncoupled from mitochondrial respiration, also known as the Warburg effect. Notch signalling is active in contexts where cells undergo glycolytic shift. We decided to test whether metabolic genes are direct transcriptional targets of Notch signalling and whether upregulation of metabolic genes can h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 53 publications
2
59
0
1
Order By: Relevance
“…It has been shown that Lin28a downregulation constitutes a developmental cue that controls metabolic rewiring in embryos that are undergoing placental development (Miyazawa et al, 2017;Shinoda et al, 2013). Metabolic transitions that are regulated by intrinsic developmental programs have also been identified in other developmental and/or organismal contexts (Agathocleous et al, 2012;Bulusu et al, 2017;Homem et al, 2014;Oginuma et al, 2017;Slaninova et al, 2016;Tennessen et al, 2011). It therefore appears that the timing of metabolic rewiring is coordinated with developmental progression via the integration of both extrinsic and intrinsic cues.…”
Section: The Emerging Roles Of Metabolism During Developmentmentioning
confidence: 99%
“…It has been shown that Lin28a downregulation constitutes a developmental cue that controls metabolic rewiring in embryos that are undergoing placental development (Miyazawa et al, 2017;Shinoda et al, 2013). Metabolic transitions that are regulated by intrinsic developmental programs have also been identified in other developmental and/or organismal contexts (Agathocleous et al, 2012;Bulusu et al, 2017;Homem et al, 2014;Oginuma et al, 2017;Slaninova et al, 2016;Tennessen et al, 2011). It therefore appears that the timing of metabolic rewiring is coordinated with developmental progression via the integration of both extrinsic and intrinsic cues.…”
Section: The Emerging Roles Of Metabolism During Developmentmentioning
confidence: 99%
“…The possibility for a ‘CD46-like’ role assigned to Notch in the mouse system is further supported by the fact that Notch is critically involved in regulating the same metabolic pathways as CD46 does in humans (Ciofani and Zuniga-Pflucker, 2005; Landor et al, 2011; Maekawa et al, 2015; Xu et al, 2015). Moreover, a recent study has identified Glut1 , and other key genes involved in the regulation of glycolysis and the tricarboxylic acid cycle, as direct transcriptional targets of Notch1 in mice (Slaninova et al, 2016). It is not clear why rodents ‘avoided’ CD46 expression during evolution.…”
Section: Intersection Of Complement With Other Key Effector Networkmentioning
confidence: 99%
“…Constitutive activation of the Notch pathway in wing imaginal discs produce deregulated growth and hyperplastic tumors (34), which depend on the induction of glycolysis-related genes such as LDH, Hexokinase A, and Glut1. Using Laconic, we analyzed intracellular lactate levels in these developing tumors, and found no significant differences in comparison to normal tissues (Fig 6A and B).…”
Section: The Warburg Effect In Drosophilamentioning
confidence: 99%